Modelo simplificado para análise de lançamento de estruturas offshore tipo jaqueta - Rodriguez, Sergio Guilhermo Hormazabal (1982)
ln the analysis of Fixed Offshore Platforms, usually the study of the launching process is performed on the final pass of the project. The standards do not stablish the conditions for this analysis. Thus the designer should proceed is based on his own experience and/or in model test results. The bibliography is reduced to very few papers, and the simplifications introduced in some of them are not necessarely justified. The main objective of the present work is to develop a mathematical theory based on 2nd Newton's law, and to implement a simplified model to test the theory and to provide a design tool to study a jacket launching in the first stage of the project. The equation is a first order differential equation, and its solution is worked out by the finite differences. Finally the results from the program developed, other computer programs, and model tests typical are compared, using data from a real case.